2011
DOI: 10.1182/blood-2011-01-329235
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after allogeneic hematopoietic cell transplantation for childhood cerebral adrenoleukodystrophy: the largest single-institution cohort report

Abstract: Cerebral adrenoleukodystrophy (cALD) remains a devastating neurodegenerative disease; only allogeneic hematopoietic cell transplantation (HCT) has been shown to provide long-term disease stabilization and survival. Sixty boys undergoing HCT for cALD from 2000 to 2009 were analyzed. The median age at HCT was 8.7 years; conditioning regimens and allograft sources varied. At HCT, 50% demonstrated a Loes radiographic severity score > 10, and 62% showed clinical evidence of neurologic dysfunction. A total of 78% (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
273
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 256 publications
(289 citation statements)
references
References 37 publications
12
273
0
4
Order By: Relevance
“…There is consensus about the efficacy of HSCT when performed early in life for MPS-IH 9,13,14 and at early stages in CALD 6,7,12,15 . Case reports suggested that HSCT might reduce demyelination in juvenile (onset between two and 14 years) and adult forms of MLD when performed as early as possible 3,4,5,16 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is consensus about the efficacy of HSCT when performed early in life for MPS-IH 9,13,14 and at early stages in CALD 6,7,12,15 . Case reports suggested that HSCT might reduce demyelination in juvenile (onset between two and 14 years) and adult forms of MLD when performed as early as possible 3,4,5,16 .…”
mentioning
confidence: 99%
“…In addition, HSCT has been mostly indicated for the cerebral form (CALD) of the peroxisomal disorder X-linked adrenoleukodystrophy (X-ALD) 2,3,4,5,6,7,8,9,10 . Considering that transplant-related mortality has declined to 10% and the rate of engraftment has substantially improved in recent years 11,12 , risk of transplant is worthwhile in contrast to the certainty that the natural history of these disorders will lead to dementia, decorticate or vegetative states and death, some years after onset.…”
mentioning
confidence: 99%
“…In particular, the association between MRI severity with disease progression and neurological/neurocognitive outcomes is well‐established 10, 28, 29. In addition, previous studies reported that boys scoring <80 on the Wechsler Performance IQ scale (a subscale available on older versions of this measure, which assessed visual reasoning and processing speed) at the time of HSCT were at greater risk for worsening neurological status after transplant 7, 8. These reports underscored the importance of initiating intervention as early as possible upon detection of active cerebral disease.…”
Section: Discussionmentioning
confidence: 99%
“…Each baseline study was reviewed by a board‐certified neuroradiologist (D.N.) and characterized according to the extent of white matter signal abnormality and atrophy using a 0–34 point severity scale developed by Loes et al6 Higher scores denote more extensive cALD, with a pre‐HSCT threshold of 10 or more points indicating “higher risk” disease status 8…”
Section: Methodsmentioning
confidence: 99%
“…Failure to detect X‐ALD may hamper the identification of affected relatives, thereby missing opportunities for early detection of Addisonism in boys and follow‐up of boys in order to provide hematopoietic stem cell transplantation in case of cerebral leukodystrophy 15 and genetic counseling.…”
Section: Discussionmentioning
confidence: 99%